Preferential Resource Spending under an Employment Guarantee : The Political Economy of MGNREGS in Andhra Pradesh - Sheahan, Megan; Liu, Yanyan; Barrett, Christopher B.; Narayanan, Sudha (World Bank, Washington, DC, 2016)
Are ostensibly demand-driven public works programs with high levels of safeguards nonetheless susceptible to political influence? This conjecture is investigated using expenditure data at the local level from India's National Rural Employment Guarantee Scheme. Focusing on one state where accountability and transparency mechanisms have been employed and implementation efforts have been widely applauded, there is no evidence of partisan-influenced spending before the 2009 election however a statistically significant but small in magnitude effect after the 2009 election. Most variation in public works expenditures is explained by the observed needs of potential beneficiaries, as the scheme intended.